Investigating the resistance of asphaltite containing hot mix asphalts against fatigue and permanent deformation by cyclic tests - Yılmaz, Mehmet; Kök, Baha Vural; Kuloğlu, Necati (My University, 2013)
In this study, the aim was to determine the in?uence of asphaltite addition on the stiffness of the hot mix asphalts as well as on their resistance against fatigue and permanent deformation through cyclic tests. The asphaltite was included as ?ller into the hot mix asphalt specimens at ?ve different proportions. The cyclic tests were performed on both the short-term aged and the long-term aged specimens. The study demonstrates that the optimal asphaltite content for utilization as ?ller with respect to volumetric design is 3% by weight. It was inferred from the results of indirect tensile stiffness modulus test that asphaltite increases the stiffness of hot mix asphalts. Similarly, the indirect tensile fatigue tests demonstrate that the use of asphaltite improves the fatigue life of the hot mix asphalts, albeit causing them to exhibit a more brittle behavior. The cyclic creep tests conducted on the specimens point out that the strength against permanent deformation increases by prolonged aging durations¸ and the mixtures display less elastic behavior with the use of asphaltite.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hot mix asphalt; Asphaltite; Fatigue; Permanent deformation; Cyclic test